Bone quality around bioactive silica-based coated stainless steel implants: analysis by Micro-Raman, XRF and XAS techniques - Ballarre, Josefina (2013)
Surface modification of surgical stainless steel implants by sol gel coatings has been proposed as a tool to generate a surface that besides being protective could also create a ‘‘bioactive’’ interface to generate a natural bonding between the metal surface and the existing bone. The aim of this work is to analyze the quality and bone formation around hybrid bioactive coatings containing glass-ceramic particles, made by sol–gel process on 316L stainless steel used as permanent implant in terms of mineralization, calcium content and bone maturity with micro Raman, X-ray microfluorescence and X-ray absorption techniques. Uncoated implants seem to generate a thin bone layer at the beginning of osseointegration process and then this layer being separated from the surface with time. The hybrid coatings without glass-ceramic particles generate new bone around implants, with high concentration of Ca and P at the implant/tissue interface. This fact seems to be related with the presence of silica nanoparticles in the layer. The addition of bioactive particles promotes and enhances the bone quality with a homogeneous Ca and P content and a low rate of beta carbonate substitution and crystallinity, similar to young and mechanical resistant bone.